Effects of Density, Morphology, and Photosynthetic Activity in Seaweeds on Nutrient Absorption from Fish Culture Effluent - Kaewduang, Boonanan; Numuean, Nittiya; Praiboon, Jantana; Chirapart, Anong (Journal of Fisheries and Environment, 2024)
The use of seaweed for nutrient absorption in aquaculture effluent has gained significant attention. This study investigated the effects of density and surface area-to-volume (SA:V) ratios of three seaweeds: Caulerpa lentillifera, Ulva rigida, and Gracilaria fisheri, on nutrient uptake in fish culture effluent. Nutrients absorption of NO2-, NO3-, NH4+, and PO43- was measured at algal densities of 10, 20, 30, 40, and 50 g·L-1 every hour over a 24 h period. Optimal absorption of NO2-, NO3- and PO43- by all three seaweeds occurred at a density of 30 g·L-1 within 24 h; with maximum removal efficiencies for C. lentillifera reaching 86.03%, 74.08%, and 100%, respectively; for U. rigida, 87.33%, 76.51%, and 100%, and for G. fisheri, 87.82%, 73.77%, and 100%, respectively. At 40 g·L-1, both C. lentillifera and U. rigida achieved 100% NH4+ removal within 20 h, while G. fisheri showed 100% NH4+ removal within 18 h at a density of 20 g·L-1. In this study, U. rigida exhibited the highest SA:V ratio (12.99±0.06 cm2:cm3), surpassing that of C. lentillifera (4.48±0.33 cm2:cm3) and G. fisheri (4.07±0.17 cm2:cm3). The SA:V ratio had a positive correlation with total nitrogen reduction, Pnet and Fv/Fm. Due to its high SA:V ratio and sheet like morphology, U. rigida was the most effective at nutrient absorption compared to the siphonous-like C. lentillifera and cylindrical, bush-like G. fisheri. These results highlight the influence of photosynthetic response on nutrient absorption with varying algal densities and SA:V ratios, identifying an optimum density of 30 g·L-1 for green algae and 40 g·L-1 for red algae.